Uncertainty comparison of three visual odometry systems in different operative conditions. (January 2016) - Pertile, Marco; Chiodini, Sebastiano; Debei, Stefano; Lorenzini, Enrico
Graphical abstract: Highlights: An experimental comparison among Visual Odometry (VO) systems is performed. VO systems with different Field of View (FOV) are analyzed. A VO system with FOV 57° × 32° exhibits lower uncertainty than one with FOV 86° × 53°. In closed spaces, a VO system with FOV 13° × 7° is outperformed by wide angle lenses. In VO, FOV 57° × 32° is more influenced by non-ideal conditions than FOV 86° × 53°. Abstract: An experimental comparison among visual odometry systems using lenses with three different focal lengths (an ultra wide angle, a medium wide angle and a telephoto lens) is presented. For each focal length, several translational and rotational tests are performed, taking into account and analyzing different positions of the system inside the laboratory. The influence of several operative parameters is analyzed, highlighting their effect on the visual odometry systems equipped with different lenses. Experimental errors and uncertainties obtained by the three systems are compared.